2006
DOI: 10.1073/pnas.0603339103
|View full text |Cite
|
Sign up to set email alerts
|

A variant of estrogen receptor-α, hER-α36: Transduction of estrogen- and antiestrogen-dependent membrane-initiated mitogenic signaling

Abstract: The status of the 66-kDa human estrogen receptor-␣ (hER-␣66) is a critical determinant in the assessment of the prognosis and in the design of treatment strategies of human breast cancer. Recently, we cloned the cDNA of an alternatively spliced variant of hER-␣66, termed hER-␣36; the predicted protein lacks both transcriptional activation domains of hER-␣66 but retains its DNA-binding domain, partial dimerization, and ligand-binding domains and three potential myristoylation sites located near the N terminus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
514
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(539 citation statements)
references
References 33 publications
17
514
3
5
Order By: Relevance
“…Estrogens, unlike what happens in the parental tumors (both in vivo and in primary cultures), where they behave as inhibitory agents, may stimulate cell proliferation. Even though preliminary data of our laboratory suggest that this difference is not related to the expression of specific ERa or ERb isoforms, we cannot rule out a role for the ERa splice variant ER 36 (Wang et al 2006). This variant has been demonstrated to be involved in cell proliferation, and the fact that it may be active only in the cell lines remains to be explored.…”
Section: Cell Linesmentioning
confidence: 96%
“…Estrogens, unlike what happens in the parental tumors (both in vivo and in primary cultures), where they behave as inhibitory agents, may stimulate cell proliferation. Even though preliminary data of our laboratory suggest that this difference is not related to the expression of specific ERa or ERb isoforms, we cannot rule out a role for the ERa splice variant ER 36 (Wang et al 2006). This variant has been demonstrated to be involved in cell proliferation, and the fact that it may be active only in the cell lines remains to be explored.…”
Section: Cell Linesmentioning
confidence: 96%
“…A previous study on the induction of ERα and ERβ in granulosa cells by activin also showed that BMP-2 increased ERα mRNA levels by approximately 50% (23), consistent with our results. Wang et al (21) reported that ERα-36 lacks both transcriptional activation domains of ERα-66, retains portions of the DNA-binding domain, the partial dimerization and ligand-binding domains, and possesses a unique 27 amino acid domain that replaces the last 138 amino acid of ERα-66. Moreover, ERα-36 can inhibit the transactivation of both ERα-66 and ERβ, stimulate the MAPK signaling pathway and induce cell growth in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the efficacy of endocrine therapy cannot be simply explained by the expression levels of ERα, but may be determined by the expression profiles of both ERα and ERβ, as well as their various splice variants (14,21,24,25). Furthermore, to understand the meaning of the demonstrated change in ERα-36 expression induced by BMP2 in breast cancer cells, additional research should be carried out to determine whether the ERα-36 reported in the present study is the same as that reported by Wang et al (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have reported that an ERa, variant called ERa,36, and not GPR30, mediates non-genomic ER signaling, including ICI agonist activity [305]. ERa,36 arises from a promoter in the first exon of ERa" but lacks both the N-and C terminal transcription activation domains, AF-I and AF-2, respectively, of full-length wild type ERa,66 [306,307]. Further studies would be required to examine ERa,36 expression in L Y2 cells.…”
Section: Resultsmentioning
confidence: 99%